1997
DOI: 10.1128/mcb.17.12.7268
|View full text |Cite
|
Sign up to set email alerts
|

E2F Activity Is Regulated by Cell Cycle-Dependent Changes in Subcellular Localization

Abstract: E2F directs the cell cycle-dependent expression of genes that induce or regulate the cell division process. In mammalian cells, this transcriptional activity arises from the combined properties of multiple E2F-DP heterodimers. In this study, we show that the transcriptional potential of individual E2F species is dependent upon their nuclear localization. This is a constitutive property of E2F-1, -2, and -3, whereas the nuclear localization of E2F-4 is dependent upon its association with other nuclear factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
179
7
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(199 citation statements)
references
References 75 publications
12
179
7
1
Order By: Relevance
“…To test this possibility, we transfected into satellite-cell derived myotubes a plasmid encoding an E2F-4 chimeric protein carrying a nuclear localization signal (E2F-4-NLS) (Muller et al, 1997). The NLS ensures that the protein is carried into the nucleus, since wild type E2F-4 is cytoplasmic (Magae et al, 1996;de la Luna et al, 1996;Lindeman et al, 1997;Muller et al, 1997;Verona et al, 1997). Similar to the other E2Fs, E2F-4-NLS did not activate S phase in myotubes (data not shown).…”
Section: E2f Does Not Activate Dna Synthesis In Td Myotubesmentioning
confidence: 86%
“…To test this possibility, we transfected into satellite-cell derived myotubes a plasmid encoding an E2F-4 chimeric protein carrying a nuclear localization signal (E2F-4-NLS) (Muller et al, 1997). The NLS ensures that the protein is carried into the nucleus, since wild type E2F-4 is cytoplasmic (Magae et al, 1996;de la Luna et al, 1996;Lindeman et al, 1997;Muller et al, 1997;Verona et al, 1997). Similar to the other E2Fs, E2F-4-NLS did not activate S phase in myotubes (data not shown).…”
Section: E2f Does Not Activate Dna Synthesis In Td Myotubesmentioning
confidence: 86%
“…For example, E2F activates its negative regulators, such as Rb, p107, p16, and p19, at the transcriptional level. Also, several groups have observed that E2F4 is regulated by cellular localization, being shuttled between the cytoplasm and the nucleus in a cell cycle-dependent fashion (Magae et al, 1996;Lindeman et al, 1997;MuÈ ller et al, 1997;Verona et al, 1997). In addition, E2F1 and E2F3 proteins have short half lives due to ubiquitin-mediated proteolysis (Flores et al, 1998;Marti et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Using this criterion, E2F4 should be as e ective an inhibitor of Ras-mediated transformation as E2F1. It has been previously noted that during S phase, when E2F target genes are expressed, E2F1 is nuclear whereas E2F4 is mostly cytoplasmic (Magae et al, 1996;Lindeman et al, 1997;MuÈ ller et al, 1997;Verona et al, 1997). To determine if the di erence in cellular localization decreases the e ectiveness of E2F4 as a Ras inhibitor, we tested an E2F4 protein fused to a consensus nuclear localization signal from the SV40 large T antigen in the focus formation assay (Lindeman et al, 1997).…”
Section: E2f Transcription Factors Inhibit Nih3t3 Focus Formation Medmentioning
confidence: 99%
“…This subgroup of E2F proteins still contains the Rb-binding sequence at the C-terminus but does not have the cdk binding or the nuclear localization sequences in the N-terminus and has nuclear export sequences instead (Dynlacht et al, 1994b;Muller et al, 1997;Gaubatz et al, 2001; Apostolova et al, 2002). Consistent with these structural features, this subgroup of E2Fs functions mainly as repressors of E2F target gene expression, and they translocate into the nucleus when in complex with the Rb family of proteins during the G0/G1 phases of the cell cycle (Muller et al, 1997;Verona et al, 1997). E2Fs 6-8, representing the remaining two subgroups, also function as transcriptional repressors (Trimarchi et al, 1998(Trimarchi et al, , 2001de Bruin et al, 2003a;Di Stefano et al, 2003;Attwooll et al, 2004b;Maiti et al, 2005).…”
Section: E2f Transcription Factors In Mammalsmentioning
confidence: 94%